A Turkish adaptation of the STEM competency beliefs instrument - Demirbağ, Cansu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
Achievement on science, technology, engineering and mathematics (STEM) education is important for the economic developments of countries. According to the social cognitive theory, the self-efficacy beliefs are a core construct which is a crucial predictor of achievement (Bandura, 1986). Self-efficacy beliefs are described as "people's judgments on their own capabilities for specific performance" (Bandura, 1986). In order to measure the self-efficacy variables in STEM education, STEM Competency Beliefs Instrument was developed by Chen, Cannady, Schunn, and Dorph at 2017. The instrument measures STEM self-efficacy beliefs of 10-14 years old students. This study aimed to adapt the instrument into Turkish and to investigate the validity of the Turkish version. The process consisted of three stages: adaptation of the instrument into a Turkish version based on expert work, a pilot study, and the main study to test the psychometric properties of the Turkish version. The instrument has 12 statements with 4 options for each. With the pilot study, reliability and validity analyses were conducted and the clarity of the items was examined. The result of the main study showed that the reliability of the instrument pointed out good internal consistency. Construct validity analysis showed that, in contrast to the original instrument, the Turkish version of the instrument has two-dimensional structure. The study concluded that the instrument can be utilized for STEM-related research to assess competency beliefs of students.|Keywords : STEM education, Self-Efficacy Beliefs, Instrument Adaptation, Construct Validity
Keywords: Science -- Study and teaching -- Turkey.; Self-efficacy -- Turkey.